2017
DOI: 10.1039/c6cc07274g
|View full text |Cite
|
Sign up to set email alerts
|

Probing the role of the backbone carbonyl interaction with the CuA center in azurin by replacing the peptide bond with an ester linkage

Abstract: The role of a backbone carbonyl interaction with an engineered Cu A center in azurin was investigated by developing a method of synthesis and incorporation of a depsipeptide where one of the amide bonds in azurin is replaced by an ester bond using expressed protein ligation. Studies by electronic absorption and electron paramagnetic resonance spectroscopic techniques indicate that, while the substitution does not significantly alter the geometry of the site, it weakens the axial interaction to the Cu A center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
(46 reference statements)
0
12
1
Order By: Relevance
“…Recently, another metalloprotein has been studied by using a similar strategy. Here, the active site of the Cu A center of azurin was probed, and the authors found that the results were opposite to those obtained with the HiPIP upon modifying a backbone carbonyl interaction. Interestingly, the A‐to‐E variant of this metalloprotein, prepared by EPL, did not lower the reduction potential of the Cu A center in azurin.…”
Section: A‐to‐e Mutations In Proteinscontrasting
confidence: 53%
“…Recently, another metalloprotein has been studied by using a similar strategy. Here, the active site of the Cu A center of azurin was probed, and the authors found that the results were opposite to those obtained with the HiPIP upon modifying a backbone carbonyl interaction. Interestingly, the A‐to‐E variant of this metalloprotein, prepared by EPL, did not lower the reduction potential of the Cu A center in azurin.…”
Section: A‐to‐e Mutations In Proteinscontrasting
confidence: 53%
“…Notably, copper ions are commonly found as the active sites in natural enzymes, such as laccase and amine oxidases. In this context, excellent works by Lu and co‐workers showed that copper is the element of choice for the design and synthesis of enzymes; however, the skeleton of these modified Cu‐containing enzymes still consists of proteins or amino acids. Thus, the development of new artificial protein‐like ligands containing anchored copper ions to mimic the activity of native enzymes is of great interest.…”
Section: Introductionmentioning
confidence: 96%
“…In this context,e xcellent works by Lu [20][21][22][23] and co-workerss howed that copperi st he element of choice for the design and synthesis of enzymes; however,t he skeleton of these modified Cu-containing enzymes still consists of proteins or amino acids. In this context,e xcellent works by Lu [20][21][22][23] and co-workerss howed that copperi st he element of choice for the design and synthesis of enzymes; however,t he skeleton of these modified Cu-containing enzymes still consists of proteins or amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…2631 Cupredoxins have been the target of many metalloprotein design efforts due to their uniquely constrained metal binding centers and spectral properties. 4,6,7,17,32 Approaches employing protein redesign using azurin as a scaffold, 20,28,3335 de novo design within three or four helical bundles, 1 , 3638 and artificial metalloproteins 39 have been explored. DeGrado et al designed a single polypeptide that formed an antiparallel 3-helix bundle called α 3 D, 40,41 and this scaffold has been modified to serve as a heavy metal binding protein, 42 capable of binding Cd(II) or iron in a tetrathiolate center.…”
Section: Introductionmentioning
confidence: 99%